A ratiometric fluorescent aptasensor based on EXPAR to detect shellfish tropomyosin in food system. (February 2023) - Zhou, Jinru; Wang, Yanbo; Zhou, Chaosheng; Zheng, Lei; Fu, Linglin
Abstract: Shellfish allergy represents a crucial public health problem, resulting in an urgent requirement for an accurate, simple, and reliable method to quantify shellfish allergens in the complex food system. Tropomyosin (TM) is known as the major allergen in shellfish. Herein, a novel switch-conversional ratiometric fluorescent biosensor, using TM-specific aptamer as the recognition probe, was developed to detect TM in the complex food system. The proposed aptasensor exhibited good accuracy, stability, and selectivity for the quantification of TM in foodstuffs. Furthermore, the applicability of this proposed aptasensor in complex food samples was verified using seven different shellfish samples. Therefore, this ratiometric fluorescent aptasensor enables accurately detecting the presence of TM traces in foods, providing technical support for allergen label supervision. Highlights: A EXPAR based-ratiometric aptasensor was developed to detect shellfish allergen TM. TM could achieve the highly specific and accurate detection. Applicability of proposed sensor in food samples was validated.